Identification of the Values of Economic Education Lampung Tribe - Putri, Rahmah Dianti; Rahmawati, Rahmawati; Rufaidah, Erlina; Winatha, I Komang; Nurdin, Nurdin (Economic Education and Entrepreneurship Journal, 2024)
The purpose of this study was to determine the general picture of the values of Family Economic Education Lampung tribe and the general pattern of the meaning of Economic Education that is applied to children within the scope of the family Lampung tribe. this study uses a qualitative design using an ethnographic approach, researchers are trying to get into the conceptual world of the subjects studied, namely the Lampung tribal family. Data collection techniques include in-depth interviews and documentation. Based on the results obtained findings 1) Piil pesinggiri regarded as self-esteem owned by the lampung tribe, Piil pesenggiri interpreted as a view of life or life guidelines Lampung tribe, 2) in managing family income, Lampung tribe family provides tanggngjawab against an isti who has full control in managing finances, 3) the implementation of Economic Education, the habit of saving from childhood, the introduction of money from an early age, the habit of saving and frugal command from parents, there is a habit to always behave based on the norms of the application of Piil Pesenggiri.Keywords: Economy, Family, Piil Pesenggiri, Lampung TribeDOI: http://dx.doi.org/10.23960/E3J/v7i1.57-62